REINFORCE BANKS PROFITABILITY BY USING DIGITAL FINANCE TECHNIQUES OF IRAQI BANKS (World Bulletin of Management and Law, 2023)
This research aims to clarify the role and importance of digital finance as one of the recent changes that occurred in the banking sector, especially the Iraqi banking sector and an indication of its role in enhancing profitability, as RealTime Gross Settlements (RTGS) and Automated Clearing House (ACH) were adopted as two dimensions of digital finance for the period (2012-2019), while it was adopted to measure the profitability variable, two dimensions, Return on Equity (ROE), and Return on Assets (ROA) for the period (2000- 2021). As three leading Iraqi banks in this field were adopted, as well as the adoption of the analytical approach in data analysis and spss 21 programming to test hypotheses, as the study found that there is a positive impact of the two dimensions of digital finance on the profit side of the research sample banks, while the study concluded that the experience of digital finance, it is still in the process of being established for the Iraqi banking sector and needs a large infrastructure to make it successful in order to ensure survival in the market and achieve a competitive advantage.